Digital clock and Azan reader / Mohd Anuar Mohd Hasan and Syed Muhd. Abd. Matin Syed Mat Daud - Mohd Hasan, Mohd Anuar; Syed Mat Daud, Syed Muhd. Abd. Matin (2005)
Time management is important for every body. For many years, the people using the device that indicates the time called ‘clock’. However, over last several decades, electronics have found extensive use in much design such as in electrical appliances, calculators, computers, machines, TV’s, game and other applications due to their low current requirement and small size. Their usage has become widespread in designing in clock that we know as digital or electronic clock. Recent development in digital technology enable to lead the generating of time setting that could required us to set the desired time (Azan reader).